Conjunctival Adenosquamous Carcinoma Lacks MAML2 Translocation: A Variant of Squamous Cell Carcinoma With Mucoepidermoid Differentiation and Aggressive Behavior?. (December 2020) - Lee, Allie; Yuen, Hunter Kwok Lai; Tham, Clement C. Y.; Cheuk, Wah
Conjunctival adenosquamous carcinoma, also known as mucoepidermoid carcinoma (MEC), is a rare tumor that preferentially affects the perilimbal area of the conjunctiva with aggressive local invasion. Consisting of infiltrative proliferation of squamous cells and mucous cells, its morphologic features are reminiscent of the salivary gland-type MEC except for the absence of intermediate cells and frequent keratin production. We reported 2 cases of conjunctival adenosquamous carcinoma and, for the first time, studied the MAML2 translocation status of this rare entity. The 2 patients were women, aged 45 and 42 years, presenting with an erythematous lesion in the left lower palpebral conjunctiva and a pigmented nodule over the left nasal conjunctiva, respectively. One tumor recurred 6 months after the initial biopsy. Excision with lid reconstruction and postoperative radiotherapy was performed for margin involvement and perineural invasion. This patient was disease free at 3-year follow-up. The other patient was lost to follow-up after tumor excision. Fluorescence in situ hybridization and reverse transcription polymerase chain reaction failed to demonstrate MAML2 translocation and CRCT1-MAML2 transcripts in both tumors. The absence of this characteristic translocation and reappraisal of the cellular composition, morphologic features, and precursor lesion suggest that conjunctival MEC may represent a variant of conjunctival squamous cell carcinoma but not related to the salivary gland-type MEC.